VARIETAL DIFFERENCES IN RESPONSE OF POTATOES TO REPEATED PERIODS OF WATER STRESS IN WINTER CROP - Kumar, Subhash; Kumar, Devendra; Minhas, J. S. (Potato Journal, 2013)
A field experiment was conducted during 2004-2005 to study the effect of repeated periods of water stress on morpho-physiological traits and tuber yield in potato cvs. Kufri Pukhraj, Kufri Chipsona1, Kufri Lauvkar and Desiree. Irrigations were applied at 15, 30, 52 and 75 DAP in the control plots and at 15, 45 and 71 DAP in the stress plots. The marketable and total tuber yields (TY) were highest in cv. Kufri Pukhraj (306 and 331 q/ha) followed by cv. Kufri Chipsona-1 (259 and 309 q/ha, respectively) under stress.Desiree had lowest TY (198 q/ha) despite higher relation water content (82.9%) and comparatively better root growth under stress. Higher resilience to water stress in cvs. Kufri Pukhraj and Kufri Chipsona-1 could be ascribed to better growth revival on re-watering and higher leaf area with high specific leaf weight (5.2 mg/cm2) during tuber development. The results indicated that varieties with greater biomass having potential for resumption of growth may be better suited for growing under sub-optimum water supply.